MEASUREMENT OF WIND POWER AND ENERGY USING AN ANEMOMETER WITHOUT MOVING PARTS - Vujicic, Bojan; Ličina, Boris; Sovilj, Platon; Vujičić, Vladimir (Journal on Processing and Energy in Agriculture, 2021)
The paper deals with the application of a newly developed anemometer without moving parts. It is digitized and has built-in electronics that convert the vibrations of two aluminum fixed frames into two digital signals: one, which shows the strength (speed absolute value)) of the wind, and the other, which shows its direction. Both of these signals are used to calculate wind power and energy. Earlier works have shown that the two-bit stochastic digital measurement method overcomes (eliminates) the problem of the offset of the analog adder. The authors of this paper apply this idea to the digital output of the sensor, where the role of the offset of the analog adder is taken over by the integral nonlinearity of the digital output of the anemometer. The first step in this direction is digitally dithering the sensor output. This principle is presented in detail, as well as a rough estimate of the accuracy gain in measuring wind energy. The obtained result shows that the accuracy in measuring wind energy is not worse than the limit accuracy in the case of a cup anemometer that generates sinusoidal voltage.
Keywords: wind power; wind energy; two-bit SDMM; anemometer with fixed frames